(untitled) (Książnica Śląska, 2025)
The article is devoted to Feliks Dłubek, the first employee of the Biblioteka Sejmu Śląskiego, later of the Śląska Biblioteka Publiczna and the Biblioteka Śląska. The author, on the basis of archival handwritten materials, reconstructs the biography of the librarian, evoking numerous facts from his life: his work as a hairdresser assistant in Germany, France and Great Britain, his service in Haller’s army during WW1, his pro-Polish activity during the plebiscite in Upper Sile-sia and his many years of employment as a librarian.